Association Between Change in Central Nocturnal Blood Pressure and Urine Albumin–Creatinine Ratio by a Valsartan/Amlodipine Combination: A CPET Study. (30th May 2018) - Fujiwara, Takeshi; Yano, Yuichiro; Hoshide, Satoshi; Kanegae, Hiroshi; Hashimoto, Junichiro; Kario, Kazuomi
Abstract: BACKGROUND: We aimed to assess the association of changes in brachial or central nocturnal systolic blood pressure (SBP) with change in urine albumin–creatinine ratio (UACR) by a valsartan/amlodipine combination (80/5 mg) therapy in hypertensive patients. METHODS: Twenty-three patients (age range, 47–78 years; mean, 68.0 years; 35% men, 65% with chronic kidney disease) with clinic brachial BP ≥140/90 mm Hg were treated with valsartan/amlodipine combination therapy for 16 weeks. At baseline and 16 weeks later, we measured brachial and central nocturnal SBP using an oscillometric Mobil-O-Graph device and UACR by spot urine in 23 patients. RESULTS: The changes in brachial nocturnal SBP ( r = 0.445, P = 0.033) and those in central nocturnal SBP ( r = 0.616, P = 0.002) were significantly associated with change in UACR by intervention. In multivariable-adjusted multiple regression analyses including changes in both brachial and central nocturnal SBP jointly, only central nocturnal SBP change retained a statistically significant association with change in UACR (β = 0.919, P = 0.020). CONCLUSIONS: Lowering central nocturnal SBP by a valsartan/amlodipine combination therapy was associated with reduction of UACR, independently of brachial nocturnal SBP reduction. Central nocturnal SBP may be a therapeutic target to protect the kidney. A larger scale interventional study will be needed to confirm the kidney protection conferred by lowering central nocturnal SBP. CLINICAL TRIALS REGISTRATION: Trial Number UMIN000013519.